Therapeutic effects of Jing Si herbal tea for chronic obstructive pulmonary disease: a comprehensive investigation from clinical to basic research - Lan, Chou-Chin; Hsieh, Po-Chun; Huang, Kuo-Liang; Yang, Mei-Chen; Liu, Guan-Ting; Kuo, Chan-Yen; Tzeng, I.-Shiang; Wu, Yao-Kuang (Frontiers in Pharmacology, 2025)
BackgroundChronic obstructive pulmonary disease (COPD), a leading cause of global mortality, significantly impairs health-related quality of life (HRQL). COPD is characterized by airway inflammation and lung tissue damage. Jing Si herbal tea (JSHT) has anti-inflammatory effects but has not been explored for treating COPD. This study investigated the potential of JSHT as an adjuvant therapy for COPD.MethodsThis study focused on patients with COPD in the exacerbation and stable phases. The control group received the standard treatment, and the JSHT group received the standard treatment plus JSHT. Both groups underwent HRQL assessments, blood tests, and cellular studies involving five different groups to assess the effect of JSHT on damage-associated molecular patterns (DAMPs) and inflammatory markers.ResultsAmong patients with exacerbations, the JSHT group showed significant improvements in HRQL, including reductions in cough, phlegm, chest tightness, breathlessness, sleep, and anxiety (all p < 0.05). Among patients with stable COPD, the JSHT group showed significant reductions in cough, phlegm, and breathlessness (all p < 0.05). Cellular studies on lipopolysaccharide (LPS)-stimulated A549 cells demonstrated that JSHT effectively reduced the release of DAMPs such as HMGB1, FPR1, and extracellular ATP, and decreased the expression of inflammatory markers including pMAPK, pJNK, NF-kB, and cCaspase 3, and pro-inflammatory cytokines like IL-1, IL-6, IL-8, and TNF-α post-LPS induction.ConclusionJSHT improved the HRQL in patients with COPD, both in stable and exacerbated states. Cellular models demonstrated a reduction in DAMPs and inflammation, suggesting the potential of JSHT as a therapeutic agent for COPD through modulation of inflammatory responses.